Preoperative Concurrent Chemoradiotherapy Versus Neoadjuvant Chemotherapy for Locally Advanced Gastric Cancer: Phase II Randomized Study - Wang, Xin; Zhao, Dong-Bing; Yang, Lin; Chi, Yihebali; Zhao, Hong; Jiang, Li-Ming; Jiang, Jun; Tang, Yuan; Li, Ning; Liu, Wen-Yang; Dou, Li-Zhou; Zou, Shuang-Mei; et al. (Frontiers in Oncology, 2022)
Abstract Objective: We evaluated and compared the efficacy and safety of neoadjuvant chemoradiotherapy (NACRT) versus neoadjuvant chemotherapy (NACT) for locally advanced gastric cancer (LAGC) in a single-center randomized phase II trial. Methods: Patients with LAGC were enrolled and received either NACT or NACRT, followed by gastrectomy and adjuvant chemotherapy. The primary endpoint was an R0 resection rate. Results: We enrolled 75 patients: 75.7% (NACT, 28/37 patients) and 76.3% (NACRT, 29/38 patients) underwent surgery; R0 resection rates were 73.0% (27/37) and 73.7% (28/38), respectively. The NACRT group had significantly better major pathological response than the NACT group (37.9% vs 17.9%, p = 0.019). Between-group postoperative complications were not significantly different. The median follow-up was 59.6 months; 5-year overall survival (OS) rate was 50.1% (NACT) and 61.9% (NACRT); neither group reached the median OS; median progression-free survival was 37.3 and 63.4 months, respectively. Conclusions: S-1-based NACRT did not improve the R0 resection rate, although it presented better tumor regression with similar safety to NACT.